Lost to follow up: a study of nonattendance at a general paediatric outpatient clinic. - Cooper, N A (1979)
50 children defined as persistent outpatient nonattenders were compared with 50 children who regularly attended the same clinics. Several factors were often found in the group of nonattenders: (a) initial referral via casualty without a letter from the family doctor, (b) hospital admission before the first outpatient appointment, (c) recognition of multiple medical problems, and (d) evidence of diffuse social problems affecting the family. 34 of the nonattenders had at least 2 of these factors, compared with only 9 children in the other group. Many of these problems can be identified at the initial consultation, and perhaps other methods of continuing health care should be provided for these children.